Effect of solution pH on solubility and some structural properties of soybean protein isolate films - Mauri, Adriana Noemi (2006)
Changes in solubility and molecular properties of protein films obtained from soy protein isolate (SPI) solutions at different pH values (2, 8 and 11) were investigated to study protein behavior during film formation. Proteins retained their native conformation in films at pH 8, but were partially or extensively denatured at pH 11 and 2. Although film protein networks were maintained by the same type of interactions at different pH values—covalent (disulfide bonds) and non‐covalent bonds (especially hydrophobic interactions and hydrogen bonds)—the intensity of each type of interaction (predicted from solubility tests in buffers with different chemical action) depended on the pH of the initial solution. Films obtained at pH 8 presented the highest solubility in all the buffers, whereas films at formed pH 2 presented the lowest, except in the buffer of pH 8 that contained urea, SDS and 2‐mercaptoethanol, which totally dissolved 100% of the film proteins. Films prepared at extreme pH values had a denser microstructure than those at pH 8. SDS–PAGE patterns indicated that films were mainly formed by β‐conglycinin and glycinin, which aggregated in different forms during film formation, depending on the pH of the initial solutions. Some of these proteins remained weakly bonded and/or were held by the network of films. These differences in the protein networks structure would affect the physical, mechanical and barrier properties of the films.